persepsi siswa terhadap upaya guru dalam pembentukan karakter siswa (suatu penelitian di SMP negeri Wilayah Aceh Besar)) - Muhammad Nurdin Fajri; Said Nurdin; Nurbaity Bustamam (Program Studi Bimbingan dan Konseling, FKIP Universitas Syiah Kuala, 2018)
Keywords: Student perception, teacher effort, character buildingThis study aims to reveal how students perceptions of teachers efforts in building the character of students in SMP Negeri in Aceh Besar Area. This type of research approach is descriptive quantitative. The sample of the study were 87 students representing three Junior High Schools of Aceh Besar. Sampling is done based on simple random sampling technique. Data collection techniques in this study were conducted using a questionnaire. Based on the results of data analysis, the findings of this study can be submitted as follows: (1) The results of data analysis on the research variables showed that students perceptions of teachers efforts in building the character of student in three SMPN Aceh Large areas are in good category. (2) In the three subvariables of moral knowing, moral feelings, and moral actions show that students' perceptions are in a very good category for aspects of moral knowing. While aspects of moral feelings and moral actions are both in good category. (3) In each item statement indicates that there are still learners who have negative perceptions of the teacher's efforts in building the character of student both in terms of moral knowing, moral feeling, and moral actions. Evident from the 45 items statement there is only one item that escaped the negative perception of students, while 44 other items still show negative perceptions of students with different frequencies and percentages. Among them 24 items with percentage 15% and 20 other items ≤ 40%.